Re-evaluating Islamic Banking Fatwas in Indonesia: Governance, Legal Certainty, and Global Harmonization in Contemporary Sharia Finance - Amiruddin, Muhammad Majdy; Hidayati, Ulfa; Rasyid, Nur Fitriani; Arwin; Faradiba, Besse (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2026)
The rapid expansion of Islamic finance has intensified scrutiny of how religious authority is institutionalized within modern regulatory systems, particularly in Indonesia where fatwas issued by the Dewan Syariah Nasional – Majelis Ulama Indonesia (National Sharia Board - Indonesian Council of Ulama) become binding only after incorporation into regulations issued by the Otoritas Jasa Keuangan (OJK) or Financial Services Authority. This study aims to re-evaluate Indonesia’s Islamic banking fatwa framework by examining its institutional translation mechanisms, degree of alignment with international standards issued by the Accounting and Auditing Organization for Islamic Financial Institutions and the Islamic Financial Services Board, and its impact on substantive maqasid realization. Using a qualitative institutional-regulatory design, the research analyzes 42 DSN-MUI fatwas, 27 OJK regulations, 18 AAOIFI standards, 12 IFSB standards, and Islamic banking portfolio data from 2015 to 2024. The findings indicate that Indonesia’s hybrid model ensures procedural legal certainty and structured fatwa-to-regulation incorporation but exhibits only partial global harmonization and a persistent dominance of debt-based contracts, reflecting a gap between formal compliance and outcome-based governance. Theoretically, the study introduces the concept of regulatory theology to explain how religious interpretation becomes embedded within the regulatory state, extending norm diffusion theory by incorporating epistemic sovereignty as a mediating variable. Practically, the research recommends stronger institutional independence, clearer codification, measurable maqasid performance indicators, and phased harmonization strategies. The originality of this study lies in reframing Islamic banking fatwa analysis from doctrinal validity toward governance-centered institutional performance grounded in empirical regulatory and portfolio evidence